2018
DOI: 10.9788/tp2018.1-14en
|View full text |Cite
|
Sign up to set email alerts
|

Marital Infi delity: The Experience of Men and Women

Abstract: This article aims to investigate the experience of infi delity in married or cohabiting men and women, considering the frequency, types of behaviors and reasons for infi delity. Participants of the study were 237 subjects, 106 men and 131 women, aged between 21 and 73 years (M=38; SD=11.22), who reported having been unfaithful to their current partner. Participants answered a sociodemographic and relationship questionnaire, the Infi delity Questionnaire and the Revised Dyadic Adjustment Scale. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
1
12
1
1
Order By: Relevance
“…In another study, it is seen that men tend to cheat significantly higher than women (Sagarin et al, 2012). However, on the other hand, there is no significant difference in deception behavior between men and women (Scheeren, Apellániz, & Wagner, 2018). In this study, the loneliness levels of married individuals did not differ significantly according to gender.…”
Section: Discussion Conclusion and Suggestionscontrasting
confidence: 57%
See 1 more Smart Citation
“…In another study, it is seen that men tend to cheat significantly higher than women (Sagarin et al, 2012). However, on the other hand, there is no significant difference in deception behavior between men and women (Scheeren, Apellániz, & Wagner, 2018). In this study, the loneliness levels of married individuals did not differ significantly according to gender.…”
Section: Discussion Conclusion and Suggestionscontrasting
confidence: 57%
“…Loneliness is seen as a condition that negatively affects the well-being of individuals but decreases with love and relationship satisfaction (Türk & Yıldız, 2017). In the literature, it is stated that individuals who are not emotionally satisfied with their marital relationship and with their spouse cannot find the closeness they are expecting begin to seek new sexual experiences, seek behaviors that may lead to betrayal against their spouse in their marriage in search of freedom (Scheeren, Apellániz, & Wagner, 2018). As it is seen in the researches, it can be said that individual and relational based problems lead to deception tendency.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Hypothesis 3 -Individuals that had been betrayed by a partner tend to have higher sexual desire, lower relationship quality, and to attribute lower importance to partner's attractiveness. This hypothesis is based on prior research that showed that individuals that have been betrayed by a partner are more likely to have extradyadic behaviors as retribution (Scheeren et al, 2018).…”
Section: Our Studymentioning
confidence: 99%
“…Research have showed that levels of general satisfaction with the relationship, sex, and the quality of love and affection are among the best predictors of extradyadic behaviors (Nowak et al, 2014;Fincham and May, 2017). Specifically, studies suggest that people engage in extradyadic behaviors because the quality of their primary relationship is low (Atkins et al, 2001;Scheeren et al, 2018). Glass and Wright (1985) found a negative correlation between relationship satisfaction and extradyadic behaviors -both emotional and sexual extradyadic behaviors -, being the strongest for relationship satisfaction and emotional extradyadic behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation